Literature Review: The Parental Pattern Review with the Wasting Occurrence on Toddlers - Aini, Nurul; Marenda, Nera (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2021)
Introduction: A wasting case is on the top rank after stunting. In 2018, the waste rate in Indonesia consisted of 10.2%. Objectives: This research aims to review the parental pattern concerning the wasting occurrence of children, especially toddlers. Methods: This research applied a literature study. The data searches were done with journal searching sites, such as Google Cendekia. The applied sample was purposive sampling. Results: Children that did not obtain immunization had 3.3 and 3.8 higher possibilities to suffer stunting and wasting than those who obtained immunization. Children without immunization had risks toward various diseases that actually could be prevented by the vaccine. Most children consumed mealy meals. Toddlers that obtained exclusive breast milk had normal status with a percentage of 80%. The dietary habits before the age of 6 years old had risks because the digesting system could not handle the complex nutrition. Thus, toddlers will be susceptible to allergens of the meals. The unprotected water source but is consumed was 57.65%. Thus, the parental pattern had correlations with the wasting occurrence, especially concerning nutrition, breast milk, immunization, and cleanliness. Conclusions: The parental pattern toward wasting occurrence specifically led to nutrition, breast milk, immunization, and cleanliness occurrences. Lack of food diversity was also the cause of the high-rate prevalence of wasting. Proper breast milk provision by mothers facilitated the nutritional balance for children and it was correlated to wasting occurrence. Lack of proper water source was also correlated to higher wasting conditions.